2013
DOI: 10.1111/jcmm.12065
|View full text |Cite
|
Sign up to set email alerts
|

An intensified systemic trafficking of bone marrow‐derived stem/progenitor cells in patients with pancreatic cancer

Abstract: Various experimental studies indicate potential involvement of bone marrow (BM)-derived stem cells (SCs) in malignancy development and progression. In this study, we comprehensively analysed systemic trafficking of various populations of BM-derived SCs (BMSCs), i.e., mesenchymal, haematopoietic, endothelial stem/progenitor cells (MSCs, HSCs, EPCs respectively), and of recently discovered population of very small embryonic/epiblast-like SCs (VSELs) in pancreatic cancer patients. Circulating CD133+/Lin−/CD45−/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 25 publications
10
54
1
Order By: Relevance
“…Among the usually examined BMSC populations, researchers share a common view that the population of BM-derived MSCs seems to be especially involved into the development and progression of (pancreatic) cancer, whereas the contributions of EPCs and HSPCs remain less evident and are rather indirect (supplemental online Table 1) [68][69][70][71][72][73][74][75][76]. These experimental observations are in agreement with our previous clinical studies of patients with gastric neoplasms and pancreatic cancer, indicating a very selective mobilization of BMSCs, mainly of VSELs and MSCs, in patients with these types of cancers [21,24].…”
Section: Contribution Of Bmscs To Pancreatic Cancer Development and Tsupporting
confidence: 88%
See 3 more Smart Citations
“…Among the usually examined BMSC populations, researchers share a common view that the population of BM-derived MSCs seems to be especially involved into the development and progression of (pancreatic) cancer, whereas the contributions of EPCs and HSPCs remain less evident and are rather indirect (supplemental online Table 1) [68][69][70][71][72][73][74][75][76]. These experimental observations are in agreement with our previous clinical studies of patients with gastric neoplasms and pancreatic cancer, indicating a very selective mobilization of BMSCs, mainly of VSELs and MSCs, in patients with these types of cancers [21,24].…”
Section: Contribution Of Bmscs To Pancreatic Cancer Development and Tsupporting
confidence: 88%
“…Interestingly, in our recent studies, we observed an intensified systemic trafficking of BMSCs in patients with gastric and pancreatic cancer. This process did not seem to be associated with the clinical stage of the disease and occurred in patients presenting with both early and advanced disease [21,24].…”
Section: Bone Marrow-pancreatic Cancer Axismentioning
confidence: 94%
See 2 more Smart Citations
“…Given that several independent groups can isolate VSEL cells and have confirmed the in vitro differentiation data [18,[31][32][33], we believe that the reasons for the differences in experimental results are of a technical nature. These differences that are outlined in great detail in a recent publication are most likely due to inadequate isolation procedures [34][35][36]. Nevertheless, some of the critiques of the VSEL cell field are valid; more systematic studies are needed.…”
Section: Fig 4 Huvsel Osseous Repair Of Craniofacial Defects (A)mentioning
confidence: 99%